Motivational Factors For Mothers Who Bring Their Babies To Baby Spa - Brahmana, Sania Tawanta Br; Paninsari, Debora; Sidabutar, Santa Greace; Tamba, Yulita Sari; Marbun, Romasta Diana; Simangunsong, Phoebe (JKM (Jurnal Kebidanan Malahayati), 2025)
Baby spa merupakan salah satu fisioterapi pada bayi dan dapat mendorong aktivitas motorik bayi dengan tujuan memberikan relaksasi pada bayi. Faktor-faktor yang memotivasi ibu untuk membawa bayinya ke baby spa sebagian besar berkaitan dengan manfaat kesehatan dan tumbuh kembang bayi serta peningkatan pengetahuan ibu. Tujuan penelitian ini adalah untuk mengetahui analisis faktor motivasi ibu yang membawa bayinya ke baby spa di Klinik Lutuna Baby Spa Pratama Ika. Jenis penelitian kuantitatif ini menggunakan rancangan penelitian survei investigatif yang dipadukan dengan metode cross sectional. Sampel penelitian sebanyak 30 orang. Uji yang digunakan adalah uji Chi Square. Hasil penelitian diperoleh nilai p= 0,000 atau berarti p<0,05, terdapat hubungan kecenderungan dengan motivasi ibu yang membawa bayinya ke Baby Spa. Nilai p=0,028, terdapat hubungan antara tumbuh kembang dengan motivasi ibu yang membawa bayinya ke Baby Spa. Kesimpulannya adalah faktor motivasi ibu yang membawa bayinya ke Baby Spa di Klinik Pratama Ika adalah faktor kecenderungan dan faktor tumbuh kembang. Disarankan kepada ibu (responden) agar lebih meningkatkan motivasi dalam meningkatkan tumbuh kembang bayi dan lebih peka terhadap masalah kesehatan bayi. Kata kunci: Motivasi Ibu, Baby Spa, Tumbuh Kembang Bayi ABSTRACTBaby spa is one of the physiotherapies in babies and can encourage the baby's motor activity with the aim of providing relaxation to the baby. The factors that motivate mothers to bring their babies to the baby spa are largely related to the health and development benefits of the baby as well as increased maternal knowledge. The objective of the study was to investigate the analysis of the motivational factors of mothers who bring their babies to the baby spa at Lutuna Baby Spa Pratama Ika Clinic. This type of quantitative research is based on an investigative survey research design combined with a cross-sectional method. The sample was 30 people. The test used is the Chi Square test. The results obtained a value of p= 0.000 or means p<0.05, there is a trend connection with the motivation of mothers who bring their babies to the Baby Spa. The value of p=0,028, there exists a connection between growth and development and the motivation of the mother who brings her baby to the Baby Spa. The conclusion is that the motivational factors of mothers who bring their babies to the Baby Spa at Pratama Ika Clinic are trend factors and growth and development factors. It is recommended for mothers (respondents) to further increase their motivation in improving the baby's growth and development and be more sensitive to the baby's health concerns. Keywords: Mom's Motivation, Baby Spa, Baby Growth and Development